(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Bread is a staple food prepared from dough of flour and water, usually by baking. Throughout recorded history, bread has been very popular around the world. It is one of humanity’s oldest foods, having been of great importance since the dawn of Agriculture. The major ingredient in bread production is wheat flour which is very expensive. The study was conducted to produce enriched bread from composite flour blend of whole wheat, soybeans, bambara nut and cashew nut seed. Four samples were produced of varying ratio mixes and then subjected to proximate, microbiological and sensory evaluation analysis. The result from the proximate analysis indicated that the nutritional value of the product increased significantly with the incorporation of flour composite. Sample A was rated highest for moisture (26%), sample B (16%) ash, sample C (18.5%) protein, (15.8%) fat respectively. Also sample C was the most accepted in terms of sensory qualities indicating improved bread quality. The result for micro biological qualities of the product indicated that the product is fit for human consumption. An enriched and nutritious adequate bread can be produced by substituting whole wheat flour with other flour composite. The study therefore based on its findings recommended that the product should be subjected for mineral and vitamin analysis to determine the micro nutrient content of the product and also its anti- nutritional composition.